Self-Consistent Renormalization as an Efficient Realization of Main Ideas of the Bogoliubov−Parasiuk R-operation - Kucheryavy, V.I. (Український фізичний журнал, 2010)
“...At the present time, the intimate connection between causality and the analytic continuation is revealed. So, it is not improbable to develop a subtraction procedure even in the most general case by the use of analytic continuation techniques.” (O.S. Parasiuk,, 1956 ). This possibility is realized explicitly and efficiently in a body of our self-consistent renormalization (SCR). The self-consistency means that all formal relations between UV-divergent Feynman amplitudes are automatically retained as well as between their regular values obtained in the framework of the SCR. Self-consistent renormalization is efficiently applicable on equal grounds both to renormalizable and nonrenormalizable theories. The SCR furnishes new means for the constructive treatment of new subjects: i) UVdivergence problems associated with symmetries, Ward identities, and quantum anomalies; ii) new relations between finite bare and finite physical parameters of quantum field theories. The aim of this paper is to expose main ideas and properties of the SCR and to describe three mutually complementary algorithms of the SCR that are presented in the form maximally suited for practical applications. “...В зв’язку з тим, що в останнiй час знайдено тiсний зв’язок мiж причиновiстю та аналiтичнiстю, не виключена ймовiрнiсть побудови вiднiмальної операцiї навiть в самому загальному випадку методами аналiтичного продовження.” (О.С. Парасюк, 1956 ). Цю можливiсть реалiзовано явно та ефективно засобами нашої самоузгодженої ренормалiзацiї (СУР). Пiд самоузгодженiстю розумiють, що всi формальнi спiввiдношення мiж УФрозбiжними фейнмановими амплiтудами також автоматично зберiгаються мiж їхнiми регулярними значеннями, знайденими згiдно з процедурою СУР. Самоузгоджена ренормалiзацiя з однаковою ефективнiстю застосовна як до ренормовних, так i до неренормовних теорiй. СУР має ефективнi засоби для конструктивного розгляду нових задач: а) ренормалiзацiйних проблем, що пов’язанi з симетрiями, тотожностями Уорда та квантовими аномалiями; б) нових взаємозв’язкiв мiж скiнченними зародковими та скiнченними фiзичними параметрами квантово-польових теорiй. Наведено огляд головних iдей та властивостей СУР, а також чiтко описано три взаємодоповнювальнi алгоритми СУР, якi подано у виглядi, максимально пристосованому для практичних застосувань.